Pengembangan Umkm Di Desa Musir Lor Melalui Pendampingan Digital Marketing Dan Legalitas (NIB) - Ilham Rahmatullah Rahmatullah; Niniek Imaningsih; Cholid Fadil (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of MSMEs in an area has its own problems and challenges, namely product marketing problems. One of them is in Musir Lor Village, Rejoso sub-district, Nganjuk Regency, East Java Province, where there are a number of MSME actors who have the potential to be developed to be more productive. But knowledge Lack of understanding of business legality is the reason why MSMEs in Musir Lor Village cannot develop on a larger scale. From the results of surveys and observations at the exact location in Musir Lor Village, data were obtained that there were several MSMEs that had the potential to develop better, but had problems in terms of marketing and business legality. Almost all MSME actors do not have insight into marketing and business legality, the marketing used is still traditional, namely word of mouth. Marketing like that creates a number of problems such as capital where MSME actors experience difficulties, because they only make products if someone orders them, if there are no orders they don't make products. When they want to make a product they have to bear the cost of production first, where payment for the product is made when the product is finished. Then the issue of business legality also includes those that affect the running of the business, legality can help businesses to increase sales. Legality makes a business more credible, because a business that has legality means it is legal and has received legal protection. Then businesses that already have legality can get People's Business Credit (KUR), and can also receive training from the government.